2021
DOI: 10.1021/acs.langmuir.1c00804
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Graphene/Nickel/Polyaniline Ternary Nanocomposites: Fabrication and Application as Electromagnetic Wave Absorbers

Abstract: The evolution of high electromagnetic absorption materials is essential in the fast growing electronic industry in overcoming electromagnetic pollution. In view of this, a series of Ni nanoparticle-decorated functionalized graphene sheets (FG/Ni) are synthesized by a solvothermal method using different ratios of FG/Ni precursors. Subsequently, FG/Ni is subjected to in situ polymerization of aniline to form FG/Ni/PANI ternary composites and characterized. The total electromagnetic interference shielding efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The total shielding effectiveness (SE T ) of the material against EMI can be defined by its ability to attenuate electromagnetic waves and is expressed in decibel (dB) units . The high value of EMI SE (dB) of a shielding material signifies less transmission of EM waves through the shielding material.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The total shielding effectiveness (SE T ) of the material against EMI can be defined by its ability to attenuate electromagnetic waves and is expressed in decibel (dB) units . The high value of EMI SE (dB) of a shielding material signifies less transmission of EM waves through the shielding material.…”
Section: Results and Discussionmentioning
confidence: 99%
“…With the nanofiller loading during in situ manufacturing, D.C. conductivity was varied in the range of 1.66-186.57. Manna et al [92] also reported on in situ polyaniline/graphene nanocomposites. The fine graphene dispersion and interaction with polyaniline led to better electrical conductivity and a high electromagnetic shielding of 65 dB.…”
Section: In Situ Polymerization To Form Polymer/graphene Nanocompositesmentioning
confidence: 99%
“…Studies were conducted on several nanomaterials, such as ferromagnetic element nanoalloys, metal oxides, ferrites and their polymers and ICP-based nanocomposites in EMI shielding applications. 276–405 The choice of magnetic materials-filled ICP nanocomposites in EMI shielding applications is mainly guided by the dielectric loss, magnetic loss and impedance matching of the component(s) of the material(s) under investigation. It provides a combination of magnetic nanoparticles and ICPs that account for its additionally reduced weight, cost, enhanced flexibility and corrosion resistance, tuneability conductivity and tailorable permeability.…”
Section: Magnetic Nanomaterialsmentioning
confidence: 99%
“…Manna and Srivastava 324 prepared polyaniline-based nanocomposites comprising Ni and functionalized graphene (FG) by in situ aniline polymerization and observed enhancement in the SE corresponding to ∼47–65 dB (2–3.8 GHz) and ∼65–45 dB (3.8–8 GHz) following absorption as the dominant mechanism. Such enhanced electromagnetic absorption could be ascribed to the impedance matching between dielectric loss and magnetic loss.…”
Section: Magnetic Nanomaterialsmentioning
confidence: 99%